Efficacy and safety of Fe-curcumin coordination polymer nanodots to prevent corneal neovascularization in alkali burn models - Yan Huo; Lele Song; Zhihui Han; Yihan Yang; Tianyao Wang; Zhao Chen; Qi Yang; Yongkang Qiu; Wenpeng Huang; Ran Tao; Liang Cheng; Lei Kang (Journal of Nanobiotechnology)
Abstract Alkali burns pose a significant risk of corneal injury, leading to potential blindness. During the progression of alkali burns, heightened oxidation levels can induce corneal damage, resulting in diminished clarity and vision loss. In this study, we chose metallic iron in conjunction with a small molecule, curcumin, to synthesize a curcumin-iron coordinated nanocomposite aimed at enhancing the bioaccessibility and targeting capabilities of curcumin. It could be found that Fe-curcumin coordination polymer nanodots (Fe-Cur CPNs) were comparably effective in suppressing corneal neovascularization, and they exhibited notable advantages in promoting corneal epithelial repair with minimal adverse effects. Additionally, Fe-Cur CPNs inhibited the activation of the nuclear factor-κ-gene binding (NF-κB) signaling pathway by scavenging reactive oxygen species (ROS), thus mitigating corneal neovascularization, which might represent a potential mechanism underlying the therapeutic effect of the Fe-Cur CPNs in alkali burn treatment. Moreover, treatment with the Fe-Cur CPNs did not result in any signs of cytotoxicity, hematological toxicity, or internal organ damage, further confirming the safety profile of this therapeutic agent. In conclusion, Fe-Cur CPNs present a novel, safe, and efficacious approach for addressing corneal alkali burns.